2001
DOI: 10.1056/nejm200104123441502
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coronary-Artery Bypass Surgery and Stenting for the Treatment of Multivessel Disease

Abstract: As measured one year after the procedure, coronary stenting for multivessel disease is less expensive than bypass surgery and offers the same degree of protection against death, stroke, and myocardial infarction. However, stenting is associated with a greater need for repeated revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
329
4
25

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 996 publications
(369 citation statements)
references
References 34 publications
11
329
4
25
Order By: Relevance
“…MI was adjudicated according to the definition in the Arterial Revascularization Therapy Study. 21 Within 1 week of the index procedure, only Q-wave MI was adjudicated as MI. Stroke at follow-up was defined as symptomatic stroke.…”
Section: Clinical End Points and Data Collection For Followup Eventsmentioning
confidence: 99%
“…MI was adjudicated according to the definition in the Arterial Revascularization Therapy Study. 21 Within 1 week of the index procedure, only Q-wave MI was adjudicated as MI. Stroke at follow-up was defined as symptomatic stroke.…”
Section: Clinical End Points and Data Collection For Followup Eventsmentioning
confidence: 99%
“…Third, other issues such as operative mortality and morbidity considerations and longer length of stay with CABG can also be important considerations. 13 Finally, most of the randomized controlled trials comparing PCI with CABG enrolled highly selected stable CAD patients who were considered suitable candidates for either procedure and who were free from major comorbidities that would be expected to preclude long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…8 These recommendations are based largely on randomized control trials enrolling patients with stable CAD. [9][10][11][12][13] However, in a subgroup analysis of the Future Revascularization Evaluation in Patients with Diabetes Mellitus: Optimal Management of Multivessel Disease (FREEDOM) trial, in which approximately one third of the cohort (n=583) was enrolled after an ACS event, the superiority of CABG in the ACS subset was comparable to the overall trial population. 11 Despite the guideline recommendations favoring CABG, previous studies have identified an implementation gap between the available evidence base and routine medical practice in patients with DM, with at least 1 in 4 eligible patients with multivessel CAD receiving PCI instead of CABG.…”
mentioning
confidence: 99%
“…In the field of ischemic heart disease, many trials examine the impact of therapy on combined clinical outcomes, including cardiovascular death, myocardial infarction (MI), stroke, unstable angina (UA) admissions, and revascularization procedures 3, 4, 5, 6, 7. Although the clinical impact of the first 3 events are of uncontested importance, it remains unclear whether nonfatal events, such as UA and coronary revascularizations, are individually associated with subsequent survival and warrant inclusion as a component of major adverse cardiovascular events (MACE).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in trials comparing percutaneous coronary intervention (PCI) with coronary artery bypass grafting for multivessel coronary artery disease, many demonstrate that the use of coronary artery bypass grafting, as compared with PCI, results in lower rates of MACE, mainly attributed to a higher rate of repeat revascularization with PCI. Given that these studies typically show no differences in hard end points (eg, mortality), but may be of insufficient duration for the full mortality benefit to be realized, more data on the long‐term prognostic significance of different MACE components are needed 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%